Aplikasi Deteksi Jumlah Orang pada Area Indoor Untuk Mendukung Pelaksanaan PPKM dengan Metode YOLO - Yoken Adinata; Kartika Gunadi; Indar Sugiarto (Universitas Kristen Petra, 2022)
Lately, the world is being hit by the Covid-19 outbreak which has caused several activities and sectors to be hampered, one of which is the buying and selling sector, both inside shopping centers and outside. Finally a solution emerged where each store was given a limit on the number of visitors to minimize the spread of the Covid-19 virus. However, there is a problem, namely monitoring the number of visitors is done manually so it is less effective and efficient.Because of the need for an application that can monitor the number of visitors when it has reached a certain limit the application will send a notification to the user. The method that used in this application to detecting the number of people is You Only Look Once (YOLO) The application has a feature so that the user can configure the parameters that will be used.Overall, the detection system used still has ambiguity in detecting small objects so that sometimes they are not detected as people. The rest, the system runs without problems from large to medium sized objects. On the other hand, overall survey respondents are satisfied with this system, this can be seen in the results of a survey taken from 15 respondents regarding the assessment of how this application helps the implementation of PPKM, and getting an average score of 8.53 out of 10, while the assessment of the ease of use of the application and user interface is 8.6 out of 10 and 8.4 out of 10.